2013
DOI: 10.1155/2013/931318
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-Assisted Transperitoneal Aortic Lymphadenectomy as Part of Staging Procedure for Gynaecological Malignancies: Single Institution Experience

Abstract: Introduction. This study was designed to confirm the feasibility and safety of robotic-assisted transperitoneal aortic lymphadenectomy as part of staging procedure for gynecologic malignancies. Methods. Chart review of 51 patients who had undergone robotic staging with aortic lymphadenectomy for different gynaecologic malignancies was performed. Results. The primary diagnosis was as follows: 6 cases of endometrial cancer, 31 epithelial ovarian cancer, 9 nonepithelial ovarian cancer, 4 tubal cancer, and 1 cervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
(23 reference statements)
1
10
0
1
Order By: Relevance
“…Despite the larger average BMI in our study, infra-renal dissections were successful in 91% of cases and the remaining 9% of cases were successfully dissected to the IMA. While console times for the aortic dissections were neither recorded in operative notes nor the database, total operative times were relatively low in this series (mean 176 ± 29 min) compared to several previous reports of hysterectomy with aortic lymphadenectomy [27,30,31; and Table 5]. One specific aspect of our port placement technique that may contribute to operative efficiency is the use of two separate laparoscopic ports for the bedside assistant surgeon.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Despite the larger average BMI in our study, infra-renal dissections were successful in 91% of cases and the remaining 9% of cases were successfully dissected to the IMA. While console times for the aortic dissections were neither recorded in operative notes nor the database, total operative times were relatively low in this series (mean 176 ± 29 min) compared to several previous reports of hysterectomy with aortic lymphadenectomy [27,30,31; and Table 5]. One specific aspect of our port placement technique that may contribute to operative efficiency is the use of two separate laparoscopic ports for the bedside assistant surgeon.…”
Section: Discussionmentioning
confidence: 91%
“…The mean time for table rotation and aortic dissection console times were 8.8 and 42 min, respectively. Using a similar dual-docking technique, Zanagnolo et al [27] subsequently reported their experience with infra-renal lymphadenctomy (aortic nodes removed 14.0 ± 6.6, BMI 23 kg/m 2 ). Potential disadvantages with the dual-docking approach include the necessity for additional laparoscopic ports, patient concerns with cosmesis, increased operative time, cost, and the coordination of the operative team during rotation of the table.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of robotic technology that facilitate surgical performances also help to shorten the learning curve, including three‐dimensional visualization, articulated instrumentation, and stability of the camera . In addition, further technological improvements have improved the versatility of its use, and robotic‐assisted laparoscopy is now a valid and diffused surgical method for treatment of gynecological cancers, even when para‐aortic lymphadenectomy is required …”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, further technological improvements have improved the versatility of its use, and robotic-assisted laparoscopy is now a valid and diffused surgical method for treatment of gynecological cancers, even when para-aortic lymphadenectomy is required. [20][21][22][23][24][25][26][27][28][29][30] In this context, we investigated the surgical outcome of the robotic approach in gynecological cancer patients undergoing pelvic surgery and aortic lymphadenectomy. All patients provided a written informed consent for their data to be collected and analyzed for scientific purpose, according to our institutional policy.…”
mentioning
confidence: 99%
“…A total of 107 and 540 search results were retrieved during the performed search in PubMed and Scopus databases, respectively, among of which 18 studies were identified as eligible for inclusion in our review [15][16][17][18][19][20][21][22][23][24][25][26][27][28][39][40][41]. One additional study was identified through hand-searching of references [38].…”
Section: Resultsmentioning
confidence: 99%